Madhhab Negotiation, Education Transformation and Conflict Resolution in Conveying the Sermon of Tablighi Jamaat in Southeast Asia - Hamdi, Saipul; Nurjannah, Siti; Nasrullah, Arif; Zuarnum, Linda Sari (UIN Sunan Gunung Djati Bandung, 2022)
The article aims to understand the phenomena of practicing madhhab in the Tablighi Jamaat (TJ) community in Southeast Asia, particularly in Thailand, Malaysia, and Indonesia. The article also investigates the madhhab negotiation between TJ members and local people where the dawah occurs in a specific context. The article also looks at changes in religious educational program developed by TJ members that tend to be informal religious education. The majority of informal religious education surrounding TJ communities is tahfiz school (memorizing the Quran). TJ members are more interested in sending their children to tahfiz school than informal school and later become Islamic priests (kyai). They are not interested to semade their children take the university level. Besides, the article also concerns exploring another role of TJ in a socio-political context where they become facilitators to overcome the Pattani Muslim conflict with the Thai government. This research was conducted for a year in 2017-2018 (March 2017-April 2018) in three countries using ethnography approach during the process of collecting data by directly involved in Tablighi Jamaat activities. The mothed of collecting data used in this research was qualitative with observative participative technique, deep interview, and documentation. The result of the research shows that Jamaah Tabligh was successful negotiating the madhhab they believe to Muslim community with different Islamic point of view. Moreover, the shifting of education orientation was emerging in TJ community, the focus was on religious exegesis without paying attention on another aspect of education for their children. Parents of TJ have pride to be called a father of a hafiz than a doctor. Another finding was Jamaah Tablig have prominent role as a reconciliatory in Pattani, South Thailand that they earned trust from Thailand Government. Amid the deadlock of reconciliation of local Muslim who want to separate from the state of Thailand with regression that created violence, bombing and arresting the activist, Jamaah tablig was there as their guarantor.